2020
DOI: 10.1186/s12909-020-02228-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a stress and anxiety coping program on objective structured clinical examination performance among nursing students in shiraz, Iran

Abstract: Background Evaluation of the competence and practical skills of nursing students, using the objective structured clinical examination (OSCE), is an integral part of the nursing education program. However, their performance could be negatively influenced by a significant level of stress and anxiety prior to the test. The present study aimed to evaluate the effect of an anxiety coping program on the OSCE performance level of first-year nursing students in Shiraz, Iran. Methods The present quasi-experimental st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…It included Relaxing activities, consuming caffeine and Soothing food. Findings of the study by Mojarrab et al [39] showed that the use of relaxation techniques along with playing soothing music reduces nursing students' test anxiety and also improves their clinical test scores. Morey and Taylor [33] reported that many students believed exercise would distract them from test anxiety and lead to be calm.…”
Section: Discussionmentioning
confidence: 99%
“…It included Relaxing activities, consuming caffeine and Soothing food. Findings of the study by Mojarrab et al [39] showed that the use of relaxation techniques along with playing soothing music reduces nursing students' test anxiety and also improves their clinical test scores. Morey and Taylor [33] reported that many students believed exercise would distract them from test anxiety and lead to be calm.…”
Section: Discussionmentioning
confidence: 99%
“…OSCE-related increased stress and anxiety could be caused by different and not before experienced examination processes and requirements, but also by the involvement of third parties, namely, assessors and simulated patients [25]. Different studies have shown that implementation of stress reduction technique prior to the OSCE would improve students' performance by maximizing their learning and practical skills [26,27]. This is something to consider in the future in order to effectively assess the knowledge, attitude, and performance of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Such a situation helped the examination committee determine that the faculty while preparing the questions are not truly adhered to the recommended and guided uniform best practices. This might pose increased exam related stress to the medical students, and reducing it might help students learn fast [ 17 , 18 ]. This prompted for organizing a FDP aiming for high quality SAQs.…”
Section: Methodsmentioning
confidence: 99%